Penerapan Model Joyful Learning untuk Meningkatkan Motivasi Belajar - Rahma Putri Damayanti; Rahmawati Rosyidah; Dhian Panggih S; Masrur Slamet; Sri Hartini; Anthony Van Dicky H (Kampus Akademik Publiser, 2025)
Learning motivation is an important factor that determines the success of students in achieving optimal learning outcomes. One of the learning models that can foster this motivation is Joyful Learning. This study aims to describe the steps, advantages, and disadvantages of applying the Joyful Learning model in learning at MTsN 1 Klaten, MAN 1 Kebumen, MTsN 3 Klaten, and MAN 2 Rembang. The research used a qualitative approach with the subject of the teacher, while the research informants were teachers who were directly involved in the learning process. Data collection techniques were conducted through interviews, observation, and documentation. The results showed that the steps of Joyful Learning include: the preparation stage by providing motivation so that students are interested in learning, the delivery stage by linking the material to real life, the training stage through fun methods such as quizzes, pictures, or animations, and the closing stage by summarizing the material with students. The advantages of this model include a more relaxed, varied learning atmosphere, increased concentration, creativity, and student activity. However, the disadvantages are that the class is difficult to control if the teacher fails to manage the learning, and the teacher is required to master many methods and have high creativity. The research concludes that Joyful Learning is worth implementing as an effort to increase learning motivation in madrasah.